USING MACHINE LEARNING ALGORITHMS TO ANALYZE GENETIC DATA FOR DISEASE DIAGNOSIS - Vladyka , Renata; Skril , Iryna (Collection of scientific papers «ΛΌГOΣ», 2023)
Today artificial intelligence (AI) plays an important role in many aspects, especially in genetics and reproductive science, including analysis of genetic data, prediction of genetic diseases, development of new methods of diagnosis and treatment. The integration of AI in medicine holds great promise for improving healthcare outcomes. With the ability to process vast amounts of data and recognize complex patterns, AI has the potential to enhance medical decision-making, accelerate diagnoses, optimize treatment protocols, and reduce medical errors. By augmenting the capabilities of healthcare professionals, AI can contribute to more precise and personalized healthcare delivery, leading to improved patient outcomes and a more efficient healthcare system.